The development and persistence of a rural craft through historical changes in market environment a case study of basketry in Barangay Bicahan, Antequera, Bohol, Philippines. - Fernandez, Estela Ocampo (149 leaves illustrations, tables, maps)
This research studies an indigenous craft within the context of expanding world capitalism as this reaches the countryside of developing countries. This study focuses on changes in basket design as indicator of changes of other factors related to basket production. These factors are studied within3 time-related frames, namely; a pre-intervention phase; a government intervention phase which came with a peak of basket production for export., The study covers the time period 1900 up to the present. The study uses the participant observation, key informant interviews, documentation of basketry items, designs and technological processes through still photographs, digital imaging and drawing illustrations. The study supports the hypothesis that changes in basket design do result as a reaction to changes in production, distribution and end-use. On the other hand, the persistence of factors related especially to an agricultural way of life. The study leads finally to recommendations which might be useful to the local practitioners of indigenous crafts.
Thesis (Graduate, Master of Arts in Anthropology) University of San Carlos, Cebu City.
Keywords: Basketry -- Bohol, Philippines